Efficient Targeted Delivery of Bifunctional Circular Aptamer‐ASO Chimera to Suppress the SARS‐CoV‐2 Proliferation and Inflammation. Issue 16 (22nd January 2023) - Yang, Gang; Zhang, Shengnan; Song, William; Bai, Xia; Li, Ling; Luo, Fatao; Cheng, Yiran; Wang, Diyue; Wang, Yanqun; Chen, Jiantao; Zhao, Jincun; Zhao, Yongyun
Abstract: Inhibition of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection and excessive inflammation is the current task in the prevention and treatment of corona vireus disease 2019 (COVID‐19). Here, a dual‐function circular aptamer‐ASO chimera (circSApt‐NASO) is designed to suppress SARS‐CoV‐2 replication and inflammation. The chemically unmodified circSApt‐NASO exhibits high serum stability by artificial cyclization. It is also demonstrated that the SApt binding to spike protein enables the chimera to be efficiently delivered into the host cells expressing ACE2 along with the infection of SARS‐CoV‐2. Among them, the SApt potently inhibits spike‐induced inflammation. The NASO targeting to silence N genes not only display robust anti‐N‐induced inflammatory activity, but also achieve efficient inhibition of SARS‐CoV‐2 replication. Overall, benefiting from the high stability of the cyclization, antispike aptamer‐dependent, and viral infection‐mediate targeted delivery, the circSApt‐NASO displays robust potential against authentic SARS‐CoV‐2 and Omicron, providing a promising specific anti‐inflammatory and antiproliferative reagent for therapeutic COVID‐19. Abstract : Chemically unmodified circular aptamer‐ASO chimera (circSApt‐NASO) that specifically inhibits SARS‐CoV‐2 replication and inflammation is developed based on an oligonucleotide therapeutic strategy. It involves the mechanism of using antispike aptamer to block S‐TLR4, and downregulation of N‐gene using antisense oligonucleotides. Due to the stability of cyclization, aptamer‐dependent, and viral infection‐mediate efficient targeted delivery, it displays robust potential against SARS‐CoV‐2 and variants.